Proteomic Analysis Revealed Metabolic Inhibition and Elongation Factor Tu Deamidation by p-Coumaric Acid in Cronobacter sakazakii - Lu, Ping; Ji, Xuemeng; Xue, Juan; Dong, Yinping; Chen, Xi (Frontiers in Microbiology, 2022)
Screening drugs and compounds to fight against Cronobacter sakazakii (C. sakazakii), one of the most common pathogens that can cause neonatal necrotizing enterocolitis, is still needed. Our previous research found that p-coumaric acid (pCA) has an inhibitory effect on C. sakazakii in vitro and in vivo. Proteomic changes of C. sakazakii BAA-894 exposed to pCA were studied in the hope of revealing the antibacterial mechanisms involved. A total of 1553 proteins were identified in C. sakazakii BAA-894 by label-free proteomics analysis. Fuzzy cluster analysis showed that 33 were up-regulated, and 110 were down-regulated with pCA treatment. GO analysis concluded that pCA caused the change of metabolic state of bacteria and generally in the state of metabolic inhibition. KEGG analysis showed that pCA inhibited energy metabolism and distorted the balance of amino acid metabolism. Posttranslational modification analysis showed that pCA affected the deamidation of three proteins, including Elongation factor Tu, one of the vital proteins in bacteria. Molecular docking suggested the hydrogen bond between the pCA carboxyl group and Elongation factor Tu Asn-64 might contribute to deamidation. Overall, we found that pCA interfered with cellular energy and amino acid metabolism and promoted elongation factor Tu deamidation, suggesting that pCA can be an effective natural substitute to control C. sakazakii.